KARAKTERISTIK PERUSAHAAN SEBAGAI DETERMINAN INTERNET FINANCIAL AND SUSTAINABILITY REPORTING - Indri Kartika; Apsarida Mila Puspa (Jurnal Keuangan dan Perbankan, 2013)
The information technological development had facilitated companies to provide and spread informationaround the world. Through websites for an example, a company could present financial and non-financialreports which ensured the stakeholders based on the going concern status of the company. This researchexamined company characteristics as the internet financial and the sustainability reporting (IFSR) determinants.The research applied non-financial company populations which had website facilities and were listed inIndonesian Stock Exchange in 2009-2010. Using a purposive sampling technique, it obtained 326 companies.The analytical data method used in this research was a multiple-regression, of which the degree of significancewas 5%. The research result showed that size, profitability, and auditor influenced significantly and positivelytoward IFSR. While, the external ownership structure and listing age of companies influenced significantlyand negatively toward IFSR. On the other hand, leverage and types of industry and listing age ofcompanies had negative influences but not really significant towards IFSR.